On the variability of precipitable water vapor and its probabilistic modeling of precipitation occurrence in Davao City - Carnicer, Kristine Mae R. (Animo Repository, 2017)
This study utilized the data files from the local radiosonde station in Davao City to monitor the atmospheric water vapor content in the area. Results of the study showed that the PWV derived from the local radiosonde station was able to provide annual, seasonal and monthly variations of the atmospheric water vapor content in Davao City. A probabilistic modeling of precipitation occurrence utilizing the PWV values was also explored in this study. REEP and logical regression analyses were performed on the three-year (2013-2015) PWV and rainfall data to determine the critical PWV value that would predict a positive or negative probability of rain occurrence. The calculation of odd ratio also showed that the odds of raining increase exponentially as PWV accumulate. © 2017 American Scientific Publishers. All rights reserved.